Use of grain sorghum as the primary grain ingredient in premium extruded foods designed for cats - Maichel, Eric W. (Kansas State University, 2021)
The effect of particle size and type of primary grain on processing and properties of extruded dry expanded cat food kibbles was investigated. Most of the diets were primarily sorghum-based. Two varieties of grain sorghum (white and red) milled at three grind sizes (0.5, 1.0 mm and 1.6 mm) were incorporated in a premium cat food formulation and processed using a pilot-scale single screw extruder. Corn- and brown rice-based formulas were also extruded as comparisons. Grind size and grain type (red sorghum, white sorghum, corn and brown rice) both had a significant (p<0.05) impact on starch gelatinization, product expansion and breaking force (F[subscript p]). The average particle size of diets was inversely correlated to extrusion specific mechanical energy (r = -0.8517; SME), enzymatically determined gelatinized starch content (r = -0.8158), piece density (r = 0.8221; inversely proportional to product expansion), and product F[subscript p] (r = 0.5670). Expansion measures such as bulk density (346.5-403.0 g/L) and sectional expansion index (3.08-3.67) indicated that the brown rice-based formulation expanded the least and corn the most, with sorghum having intermediate expansion when grind size was the same. Specific Mechanical Energy (SME) ranged from 105.4-183.1 kJ/kg depending on grind size and grain variety and seemed to be one of the determinants of kibble properties such as expansion. Raw material physico-chemical properties such as gelatinization onset temperature (T[subscript o]; 66.7-78.3°C) determined using differential scanning calorimetry and pasting temperature (T[subscript paste]; 76.6-81.5°C) obtained from rapid visco-analyzer also appeared to have an impact on expansion, as observed from their correlations with bulk density (r= 0.8125 and 0.7742, respectively). These observations support that although the SME input is important as the driving force, having a matrix that has film forming or extensibility properties is also critical for product expansion. Lower To and Tpaste indicated a greater propensity for starch gelatinization and degradation, as seen from the negative correlations with respect to enzymatically obtained gelatinized starch (r= -0.5844 and -0.6085, respectively). This was the reason for connecting T[subscript o] and T[subscript paste] to matrix extensibility and expansion. The negative correlation of particle size with expansion was thus clearly explained, as an increase in grind size negatively impacted both the driving force for expansion and matrix extensibility. The lower surface area per unit volume of particles with higher grind size possibly led to poor heat and moisture penetration during preconditioning and extrusion, and thus negatively affected film forming ability and expansion. Similarly grain type also impacted both driving force and extensibility, and thus expansion. For example, the brown rice-based formulation, which had one of the lowest expansions of all grain varieties, also had one of the lowest SME inputs (161.2 kJ/kg) and gelatinized starch content after extrusion (30.7%). The textural attribute of kibble F[subscript p] was found to have a positive correlation with piece density (r= 0.7059), which aligned with the theory of mechanical strength of porous matrices that dictates that the strength of cellular products is inversely proportional to cell wall size or in other words expansion. Results show that overall, a larger particle size raw material flows faster through the extruder (at the same volumetric setting as a smaller particle size), leads to lower SME, higher Specific Thermal Energy (STE), a higher STE : SME ratio and lower overall energy consumption than smaller particle size material. The measured and also the calculated dry feed rates confirmed the observation for material flow rate above, higher throughput implies faster flow rate. Sensory properties such as color, fracturability, fibrousness and grittiness were related with product palatability tests using cats and product properties such as peak breaking force (Fp) and degree of cooking. It was concluded the color of the final product based on differences of grain ingredient and the peak breaking force seemed to have the biggest impact on palatability and product sensory properties. In vivo digestibility and colonic fermentation results using cats were also related to product attributes.
Keywords: Extrusion; Cats; Particle size; Mass balance; Energy balance; Pet food